Development of Action and the Clinical Continuum - Brian Hopkins (Neural Plasticity)
The development of action is depicted as consisting of changes in the task-specific couplings between perception, movement, and posture. It is argued that this approach may provide a much needed basis from which attempts can be made at theoretically unifying the constituents of the clinical continuum (viz., early detection, diagnosis, prognosis, and intervention). Illustrative examples germane to this approach are given with regard to how posture serves as a constraint on the emergence of reaching movements and how cortical development influences the coordination of leg movements as revealed by a study involving infants with white matter lesions. Particular attention is paid to early detection and it is recommended that further improvements to this aspect of the clinical continuum can be derived from combining serial qualitative and quantitative (kinematic) assessments with brain-imaging techniques. It is emphasized that quantitative assessments should incorporate experimental manipulations of perception, movement or posture during transitional periods in development. Concluding comments include consideration of the timing of early intervention.